MiRNA-27a Transcription Activated by c-Fos Regulates Myocardial Ischemia-Reperfusion Injury by Targeting ATAD3a. (9th August 2021) - Bao, Yandong; Qiao, Ying; Yu, Hang; Zhang, Zeying; Yang, Huimin; Xin, Xin; Chen, Yuqiong; Guo, Yuxuan; Wu, Nan; Jia, Dalin
Abstract : MicroRNA-27a (miR-27a) has been implicated in myocardial ischemia-reperfusion injury (MIRI), but the underlying mechanism is not well understood. This study is aimed at determining the role of miR-27a in MIRI and at investigating upstream molecules that regulate miR-27a expression and its downstream target genes. miR-27a expression was significantly upregulated in myocardia exposed to ischemia/reperfusion (I/R) and cardiomyocytes exposed to hypoxia/reoxygenation (H/R). c-Fos could regulate miR-27a expression by binding to its promoter region. Moreover, overexpression of miR-27a led to a decrease in cell viability, an increase in LDH and CK-MB secretion, and an increase in apoptosis rates. In contrast, suppression of miR-27a expression resulted in the opposite effects. ATPase family AAA-domain-containing protein 3A (ATAD3a) was identified as a target of miR-27a. miR-27a regulated the translocation of apoptosis-inducing factor (AIF) from the mitochondria to the nucleus and H/R-induced apoptosis via the regulation of ATAD3a. It was found that inhibiting miR-27a in vivo by injecting a miR-27a sponge could ameliorate MIRI in an isolated rat heart model. In conclusion, our study demonstrated that c-Fos functions as an upstream regulator of miR-27a and that miR-27a regulates the translocation of AIF from the mitochondria to the nucleus by targeting ATAD3a, thereby contributing to MIRI. These findings provide new insight into the role of the c-Fos/miR-27a/ATAD3a axis in MIRI.